The effect of property contrast in two-component piezoelectric composites - Huber, JE; Faheem Ahmed, NTA (Elsevier, 2024)
A Mori - Tanaka model of piezoelectric composites is used to study the effect of property contrast between the components of a two-component composite. The composite comprises a piezoelectric matrix and piezoelectric inclusions whose property values are scaled from those of the matrix. The scaling method allows a wide range of material combinations to be approximated without using explicit properties of specific materials. Additionally, the aspect ratio and volume fraction of inclusions is varied to seek optimum values of the piezoelectric coefficients in the composite. It was found that scaling the properties in the electroelastic moduli reveals significant results for the piezoelectric performance coefficients dhgh, κ33, g33 and kt. By varying the material scaling factors alongside the inclusion aspect ratio it is demonstrated that giant enhancements of the transducer figure of merit dhgh could potentially be achieved through composite design. This approach identifies some novel opportunities for optimised piezoelectric composites.